Examine The Constitutionality Of Regulations Under Laws That Are Not Contrary To The Law But Contrary To The Constitution - Aditya Yuli Sulistyawan; I Putu Eka Cakra (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2020)
Kewenangan untuk memeriksa UU terhadap Konstitusi dilakukan oleh Mahkamah Konstitusi dan pengujian hukum dan peraturan berdasarkan Undang-Undang tentang Hukum dilaksanakan oleh Mahkamah Agung sebagaimana diatur dalam Pasal 24 A paragraf 1 dan 24 C paragraf 1 Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Namun, dalam perumusan pasal a quo ternyata masih menyisakan masalah, yaitu belum mengatur mekanisme pengujian norma yang terkandung dalam undang-undang di bawah undang-undang jika ternyata tidak bertentangan dengan undang-undang tetapi bertentangan dengan konstitusi. Tulisan ini membahas pengujian norma-norma undang-undang melalui Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 tentang kewenangan peradilan di casu a quo pasal 24 A ayat 1 dan 24 C ayat 1 Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Kata kunci: otoritas, hukum, konstitusi. Abstract The authority to examine the Law against the Constitution is carried out by the Constitutional Court and the testing of the laws and regulations under the Law on the Law is carried out by the Supreme Court as regulated in article 24 A paragraph 1 and 24 C paragraph 1 of the 1945 Constitution of the Republic of Indonesia. However, in the formulation of the article a quo it turns out still leaves a problem, namely not yet regulating the norm testing mechanism contained in the legislation under the legislation if it turns out it is not contrary to the law but contrary to the constitution. This paper analyzes the testing of the norms of the legislation through the 1945 Constitution of the Republic of Indonesia Republic IX concerning judicial authority in casu a quo article 24 A paragraph 1 and 24 C paragraph 1 of the 1945 Constitution of the Republic of Indonesia. Keyword: authority, law, the constitution.